A Review of The Age of Sustainable Development by Jeffrey Sachs - Kahn, Matthew E. (Journal of Economic Literature, 2015)
How does economic science inform the study of sustainable development? In his new book, Jeffrey D. Sachs analyzes the challenges of achieving economic growth while protecting the environment and achieving an equitable distribution of resources. This review presents an overview of this ambitious book with special emphasis on the role of the objectives of local and national leaders and their incentives to pursue the sustainability agenda. Given the huge migration to cities now playing out in the developing world, special attention is paid to the role of urbanization as a cause of sustainability opportunities and challenges. (JEL Q01, Q54, Q56, R11)